2018
DOI: 10.1245/s10434-018-6506-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic Activity Score to Assess Anticancer Immunity in Colorectal Cancer

Abstract: High CYT within CRC is associated with improved survival, likely due to increased immunity and cytolytic activity of T cells and M1 macrophages. High CYT is also associated with high expression of ICMs; thus, further studies to elucidate the role of CYT as a predictive biomarker of the efficacy of immune checkpoint blockade are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 49 publications
9
107
2
Order By: Relevance
“…Multiple studies have shown that infiltration of immune cells into the tumor microenvironment is a prognostic factor in cancer. Recent studies focusing on tumor immune cytolytic activity also demonstrated that transcript levels of two key cytolytic effectors, GZMA and PRF1 , correlate with patient survival . In this study, using transcriptome profiling data, we estimated immune cell composition and cytolytic activity in SCCOT, clinically tumor‐free tongue tissue from SCCOT patients and control tongue tissue from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that infiltration of immune cells into the tumor microenvironment is a prognostic factor in cancer. Recent studies focusing on tumor immune cytolytic activity also demonstrated that transcript levels of two key cytolytic effectors, GZMA and PRF1 , correlate with patient survival . In this study, using transcriptome profiling data, we estimated immune cell composition and cytolytic activity in SCCOT, clinically tumor‐free tongue tissue from SCCOT patients and control tongue tissue from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that patients with high cytolytic activity in tumor‐free tongue had improved survival compared with patients with low cytolytic activity. Cytolytic activity in tumors has been shown to correlate with mutation load and number of predicted neoantigens . Oral SCC, including SCCOT, is a paradigm of Slaughter's concept of ‘field cancerization’ , in which tumors are thought to arise from an expanded pool of genetically altered pre‐neoplastic cells .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor gene expression and corresponding clinical data for the TCGA-BRCA project were obtained from the Pan-Cancer Clinical Data Resource [39] and through cBio Cancer Genomic Portal [40], as we previously reported [41][42][43][44][45]. Data for the 1065 female patients were analyzed in the study.…”
Section: Data Of the Cancer Genome Atlas Breast Cancer Cohortmentioning
confidence: 99%
“…Measurements of immune activities like T cell receptor diversity and relative fractions in tumors of different types of immune cells were estimated from tumor gene expression with CIBERSORT, a bioinformatic algorithm 34 . Immune cytolytic activity in tumors was defined as the geometric mean of grandzyme A (GZMA) and Perforin 1 (PRF1) expression values in transcripts per million (TPM), as described previously 36,37 . In order to confirm correlation between CYT and grandzyme B (GZMB) or Interferon (IFN)-gamma, Spearman correlation was calculated, which demonstrated r = 0.819 (p < 0.01) and r = 0.789 (p < 0.01), respectively ( Supplementary Fig.S1).…”
Section: Analysis Of Gene Expression Datamentioning
confidence: 99%